Detection of mullerian duct anomalies: diagnostic utility of two dimensional ultrasonography as compared to magnetic resonance imaging - Senger, Krishna Pratap Singh; Singh, Ajay K.; Sharma, Vivek; Singh, Ankita; Ravikumar, R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Mullerian duct anomalies (MDAs) are a fascinating group of disorders that have varied clinical presentation from being asymptomatic to primary amenorrhea to inability to reproduce. Correct diagnosis of the condition plays a crucial role in management. Imaging plays a pivotal role in making correct diagnosis. This study aims to find the prevalence of MDAs amongst study population and their relation with infertility and also compares diagnostic utility of pelvic ultrasound with MRI. Methods: A randomized diagnostic test evaluation study was conducted in the Department of Radiodiagnosis and Imaging of a tertiary care teaching hospital over a period of 2 years. The patient first underwent pelvic 2D USG in multiple planes using curvilinear probe of 3MHz to 5 MHz. frequency and then MRI. Results: Most common MDA in total study sample and in primary infertility group is arcuate uterus while in recurrent abortions group it is unicornuate uterus. Out of total study sample of 75 patients 2D USG detected 18 cases of MDA while MRI detected 22 cases of MDA. So, 2D USG failed to detect 04 cases of MDA in total study population bringing overall sensitivity of 2D USG as 81.8%, specificity of 100%, PPV of 100%, NPV of 93.4% and accuracy of 94.6%. Conclusions: 2D USG has a few limitations but in view of relatively simple imaging procedure, ease of availability and cost effectiveness it should be utilized as an initial imaging modality in patients with suspicion of MDAs.